Speedy beauty dryer / Rezza Quhairie Abd Rahman...[et al.] - Abd Rahman, Rezza Quhairie; Abdul Rahman, Nur Qamarina; Samsudin, Nurul Nadia; Ahmad Za'im Faisal, Dayang Nor Deanna Yusrina (2018)
Nowadays, most women wear makeup and they use makeup brushes to apply and blend their makeup. These makeup brushes must be cleaned for at least once a week to make sure that the makeup does not accumulated at the brush and makes it difficult to apply makeup properly. These makeup brushes usually took one night to dry after washing it and this will cause problems to the user if they need to use the makeup brushes. Besides that, by letting the makeup brushes to dry on its own might cause bacteria to breed on the makeup brushes because the makeup brushes are moist and bacteria are more likely to breed in moist condition. To fix this problem, Speedy Beauty Dryer is invented to allow the targeted customer to dry their makeup brushes faster after cleaning and to dry the brushes in a more convenient way. Generally, this product will enter the market by meeting the customers need to save time when they would like to apply their makeup. This product is able to penetrate the market because there are plenty of women who wears makeup and use makeup brushes.